Simultaneous Study of the Growth and Grazing Mortality Rates of Microbial Food Web Components in a Mediterranean Coastal Lagoon - David Pecqueur; Justine Courboulès; Cécile Roques; Sébastien Mas; Romain Pete; Francesca Vidussi; Behzad Mostajir (Diversity, 2022)
The abundances of 17 cytometric groups encompassing four groups of bacteria, three groups of cyanobacteria, six groups of eukaryotic picophytoplankton (<2–3 µm), and four groups of small eukaryotic nanophytoplankton (between 3 and 6 µm) were studied in the Thau Lagoon across different seasonal conditions. Among them, the growth (µ) and mortality rates due to grazing (g) of 12 groups of bacteria, cyanobacteria, and eukaryotic pico- and nanophytoplankton were simultaneously studied in the Thau Lagoon via four dilution experiments across different seasonal conditions. The abundances of heterotrophic flagellates and ciliates and their potential predators were studied and linked to prey mortality. Bacteria were more active than phytoplankton and displayed the highest growth and grazing mortality rates. Most studied groups had g:µ ratios > 1, suggesting that predators efficiently grazed and transferred these preys. Surprisingly, the observed variations in predator abundance across seasons did not necessarily correspond with changes in grazing pressure. The significant positive relationship found between water temperature and bacterial grazing mortality rates and the reverse trend observed for larger eukaryotic prey suggested that warmer water increases small prokaryote transfer to higher trophic levels but disadvantages larger eukaryotic prey transfer.